Initial experience with Impella RP in a quaternary transplant center. Issue 5 (10th January 2020) - Monteagudo‐Vela, María; Simon, Andre; Panoulas, Vasileios
Abstract: Right ventricular failure is one of the most common complications encountered after left ventricular assist device implantation and heart transplantation. It has been reported to have an incidence up to 30%. It increases morbidity and short‐term mortality. Impella RP is a small pump that can provide up to 4L/min of flow. We analyzed all the patients with right ventricular failure that were treated with Impella RP in our institution. The Impella RP was implanted percutaneously in the catheterization laboratory guided by fluoroscopy. Overall, 7 patients required the implantation of an Impella RP due to right ventricular failure: 2 after long‐term LVAD, 3 presented with acute right ventricular failure immediately after LVAD implantation, and 2 needed it after heart transplantation. Regarding complications, we report 2 patients with hemolysis. Hemodynamic parameters as well as end‐organ perfusion and inotropic requirements improved after the insertion of the Impella. Overall, 30‐day survival is 58%. Median time of support was 9 (5–19) days. RV failure is one of the most challenging complications after LVAD implantation and heart transplantation. The major challenge is the timing of implantation. The minimally invasive nature of the Impella RP facilitates de‐escalation of treatment and paves the road to recovery. Impella RP proved useful in facilitating ECMO wean. Used in a prompt manner alongside the ease of implantation and the minimal rate of complications, Impella RP seems to be an appropriate device to tackle RV failure providing enough flow to allow for recovery or escalation decision‐making.